2018
DOI: 10.1016/j.cell.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

The THO Complex Coordinates Transcripts for Synapse Development and Dopamine Neuron Survival

Abstract: Synaptic vesicle and active zone proteins are required for synaptogenesis. The molecular mechanisms for coordinated synthesis of these proteins are not understood. Using forward genetic screens, we identified the conserved THO nuclear export complex (THOC) as an important regulator of presynapse development in C. elegans dopaminergic neurons. In THOC mutants, synaptic messenger RNAs are retained in the nucleus, resulting in dramatic decrease of synaptic protein expression, near complete loss of synapses, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…Considering cells involved in the context of locomotion control and food responses, with numerous connections to AVK, a network becomes apparent, comprising the neurons AVK and DVA, downstream SMB (connected to AVK and DVA by electrical and chemical synapses), and upstream dopaminergic PDE (Figure 6A). PDE neurons sense the texture of bacteria and, jointly with CEP and ADE neurons, are involved in the ''basal slowing response'' when animals enter a bacterial lawn (Maeder et al, 2018;Sawin et al, 2000).…”
Section: Avk Resides Within Neural Circuits Regulatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering cells involved in the context of locomotion control and food responses, with numerous connections to AVK, a network becomes apparent, comprising the neurons AVK and DVA, downstream SMB (connected to AVK and DVA by electrical and chemical synapses), and upstream dopaminergic PDE (Figure 6A). PDE neurons sense the texture of bacteria and, jointly with CEP and ADE neurons, are involved in the ''basal slowing response'' when animals enter a bacterial lawn (Maeder et al, 2018;Sawin et al, 2000).…”
Section: Avk Resides Within Neural Circuits Regulatingmentioning
confidence: 99%
“…If no food is found, after 10 min, behavior is altered to long, straight runs, covering larger distances (dispersal; Bhattacharya et al, 2014;Gray et al, 2005). Upon food encounter, DA is released by mechanoreceptive CEP and ADE head neurons (Kang et al, 2010) and from the midbody PDE neurons (Maeder et al, 2018). On food, animals switch to a behavior termed dwelling: slow, mostly forward locomotion with frequent reversals (Flavell et al, 2013;Fujiwara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also showed regulation of CREB/CRH-1 by KIN-1/KIN-2, the nematode homologs of the regulatory and catalytic subunits of cAMP-dependent kinase PK-A (Rojo Romanos et al 2017), which might determine the speed of developmental modifications in some neurons in the nerve cord (Yu et al 2017). At least in some scenarios (such as synapse development in the nematode) PK-A -regulated CREB/CRH-1 activity is independent of CRTC, further supporting the division of CREB functions into subgroups of target genes, only some of which requiring CRTC (Maeder et al 2018). Similarly, CBP/CBP-1 cooperates with CREB/CRH-1 in many cells (Eastburn and Han 2005), and protects neurons from polyglutamine-induced neurodegeneration (Bates et al 2006).…”
mentioning
confidence: 98%
“…There were 40 overlapping blood-secretory proteins between PPD and AutismKB database ( Figure 4C , Supplementary Table 9 ). After literature survey on the four genes, we found that RARS and THOC5 had been reported related to brain development ( 35 , 36 ).…”
Section: Resultsmentioning
confidence: 97%